Subjective Well-Being Guru: Pengaruh Keterlibatan Siswa dan Refleksi Terstruktur melalui Model SALAM di Kelas Merdeka - Astuti, Sri Widya; Fadilah, Risydah; Dewi, Salamiah Sari (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study evaluates the effectiveness of the SALAM learning model in enhancing teachers' subjective well-being (SWB). The SALAM model, consisting of five steps (Teaching Enthusiasm, Asking Questions About Feelings, Actively Engaging Students, Analyzing the Learning Process, and Monitoring Learning Outcomes through Reflection), is designed to facilitate teachers' roles as learning leaders. The research employed a quasi-experimental method using a cluster randomized pretest and posttest control group design. The results showed that the SALAM model training significantly improved teachers' subjective well-being, with an alpha value of 0.03. The experimental group scored higher (3.00) compared to the control group (0.90). Teachers' subjective well-being includes improvements in job satisfaction, teaching efficacy, and school connectedness through positive collaboration. The SALAM learning model simplifies teachers' tasks in leading classroom learning and enhances their professional competence. Increased teaching skills positively affect teachers' confidence in teaching, ultimately boosting their subjective well-being. The study's implications indicate that implementing the SALAM model in teacher training programs can improve teaching quality and teaching happiness. Further research is needed to evaluate the sustainability of the intervention's effects over the long term.